PELAKSANAAN PENGAWASAN PADA PEDAGANG KAKI LIMA OLEH PEMERINTAH KOTA SURAKARTA TERHADAP MAKANAN STREET FOOD SEBAGAI UPAYA MEWUJUDKAN PEMENUHAN HAK-HAK KONSUMEN - Purwono Sungkowo Raharjo; Rosita Candrakirana; Solichah Novyana Putri (Academy of Education Journal, 2023)
Street vendors are one of the business actors who are sought after by the public, especially those who sell or provide street food. In the city of Surakarta, street vendors are much sought after by both domestic and foreign tourists because the city of Surakarta is known for its culinary tours which serve typical Solo food. In the arrangement of street vendors, the city of Surakarta has made Regional Regulation No. 3 of 2008 concerning Management of street vendors. The problem to be studied is regarding the implementation of supervision on street vendors by the Surakarta city government. This research is a normative research using a statutory approach (statute approach) accompanied by the results of interviews with the Department of Industry and Trade and the Health Office of Surakarta City. Based on the results of the research that the rights that have been regulated in UUPK must be fulfilled to guarantee the safety and health standards of the food. Especially fulfilling the right to comfort, security and safety in consuming goods and/or services, in this case, is "street food". And the implementation of supervision of street vendors by the Surakarta city government has not been carried out routinely or periodically. For this, it is necessary to have direct and periodic supervision by the Surakarta city government so that consumer rights are fulfilled in terms of safety and health.